PERBANDINGAN TINDAKAN MENJAGA KEBERSIHAN RONGGA MULUT DAN STATUS ORAL HYGIENE PADA ANAK USIA SEKOLAH DASAR DI DAERAH PERKOTAAN DAN PEDESAAN - Dewi Saputri; Cut Fera Novita; Muhammad Zakky (Journal of Syiah Kuala Dentistry Society, 2017)
Oral hygiene is one of local factor that affects the most and could causes any dental problems. Oral hygiene status of individual or groups, one of them is affected by behaviour. Taking care of oral hygiene is a part of preserving oral health condition behaviour by controlling dental plaque which is aimed to dental plaque removal and prevent the accumulation of the dental plaque, food debris and stain removal, stimulating gingival tissue, and covering teeth surface with fluor that would affect oral hygiene status. The aim of this study is to know the ratio of oral hygiene preservative behaviour and oral hygiene status on children of elementary school age in urban and rural area. This study is a cross-sectional study. Method of sampling is pusposive sampling which included 30 subjects from urban area (MIN Mesjid Raya) and 30 subjects from rural area (MIN Durung). This study was done by using questionnaires of oral hygiene practices and oral hygiene status examination using OHI-S. Analysis result using chi-square test revealed significant ratio between oral hygiene practice and oral hygiene status on children of elementary school age in urban and rural area (p0.05). The conclusion of this study is oral hygiene practices and oral hygiene status at elementary school age children in urban areas are better than elementary school age children in rural areas.Keywords : Oral hygiene, dental plaque control, OHI-S, urban, rural.